2003
DOI: 10.1152/physiolgenomics.00169.2002
|View full text |Cite
|
Sign up to set email alerts
|

Lack of vascular connexin 40 is associated with hypertension and irregular arteriolar vasomotion

Abstract: Gap-junctional communication coordinates the behavior of individual cells in arterioles. Gap junctions are formed by connexins 40 (Cx40), Cx43, Cx37, and Cx45 in the vasculature. Previously, we have shown that lack of Cx40 impairs conduction of dilatory signals along arterioles. Herein, we examined whether hypertension is present in conscious animals and whether this is a direct effect or due to secondary mechanisms. Mean arterial pressure was elevated by 20–25 mmHg in conscious Cx40-deficient mice (Cx40−/−) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
155
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(164 citation statements)
references
References 31 publications
8
155
0
1
Order By: Relevance
“…The physiological importance of connexin 40 has been identified in a number of studies reporting that a loss of connexin 40 (either through genetic mutation or connexin 40 inhibitors) results in an increase in blood pressure and a loss of vasocontrol [42,43]. The inhibition of gap junction communication with connexin-mimetic peptides 40 Gap27 or 43 Gap27 has been shown to block EDHF-mediated signal transmission in vivo, indicated by the abolition of NAME-and indomethacin-resistant renal vasodilation [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological importance of connexin 40 has been identified in a number of studies reporting that a loss of connexin 40 (either through genetic mutation or connexin 40 inhibitors) results in an increase in blood pressure and a loss of vasocontrol [42,43]. The inhibition of gap junction communication with connexin-mimetic peptides 40 Gap27 or 43 Gap27 has been shown to block EDHF-mediated signal transmission in vivo, indicated by the abolition of NAME-and indomethacin-resistant renal vasodilation [43].…”
Section: Discussionmentioning
confidence: 99%
“…The results of studies conducted using connexin 40-deficient mice have also emphasised the importance of gap junctions, specifically, those associated with connexin 40, in the normal physiological transmission of endothelium-dependent vasodilation [44]. This set of studies showed that a lack of connexin 40 leads to the development of hypertension, and to irregular vasomotion in resistance arteries [42]. Another important outcome of these studies was the finding that the vessels needed to be locally stimulated with acetylcholine for the attenuated propagation along the endothelium to become apparent.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Genetic ablation of Cx40 causes severe impairment of conducted vasodilator responses in arterioles, 3,4 uncoordinated vasomotion, 5 and hypertension. [5][6][7] Furthermore, vascular expression of Cx40 is reduced in genetically hypertensive rats. 8 Within the kidney, gap junctions are prevalent in the juxtaglomerular apparatus (JGA).…”
mentioning
confidence: 99%
“…Studies in knockout mice indicate that Cx40 has an important role in vascular development and blood pressure regulation (Figueroa and Duling, 2009). Ablation of Cx40 produced hypertension associated with irregular vasomotion, and interfered with the regenerative component of conducted vasodilation (de Wit et al, 2003). Thus increased expression of Cx40 protein in cerebral arteries 24 h after TBI may improve coordination of vasomotor tone and conduction of vasodilation signals, thereby contributing to restoration of vessel function, and thus may be a protective response to injury and a possible treatment target.…”
Section: Discussionmentioning
confidence: 99%